Taking a stand against human rights abuses - Kronenwetter, Michael (New York : F. Watts, 1990)
Discusses governments that abuse human rights and suggests what one can do to voice opposition to these oppressive regimes.
Includes bibliographical references (p. 151-152).
Keywords: Civil rights -- Juvenile literature; Human rights -- Juvenile literature; Human rights